Perancangan Sistem Attendance Mahasiswa Dan Peminjaman Alat Lab Berbasis RFID Di Politeknik Manufaktur Negeri Bangka Belitung - Afriansyah, Afriansyah; Afriansyah, Riki; Riezky Pratiwi, Indah (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Attendance is an attendance list that is always used to view attendance data at an institution that wants to use it, because attendance has a value that is relevant enough to be used. In achieving data relevance for absenteeism, careful planning, effective management, and compliance with regulations and requirements are required. However, attendance at the Bangka Belitung State Manufacturing Polytechnic is still done manually. The conditions used greatly influence the technology used. Therefore, we need an attendance tool based on modern technology, namely RFID, which can be used to register attendance which is carried out by developing a system using the Prototype method. So with this RFID-based attendance system it can help the work of those in charge of managing attendance data.